ANTICOLONIAL REVOLT IN XXI ST CENTURY BOLIVIA: THE CONTINUANCE OF “ INTERNAL CONFLICT” AND THE DEFEAT OF NEOLIBERAL PARTIES 2000-2003 - Choque Mendoza, Fredy (Revista de Historia Social y de las Mentalidades, 2024)
In order to explain the “changing process” that  is nowadays experiencing Bolivia is necessary  to go back to the origins of contemporary ethnic  nationalism (post-52 period). In this socio-poli - tical rising process the whole of the indigenous  movement has contributed, starting from diverse  ideological positions and directing towards an  horizon of self-determination in the beginning of  the XXIst century. This process expresssed itself  in the knowned as “Water Conflict” (2000) and  finally in the “Gas Conflict” of 2003 by means  of a general urban and rural indigenous uprise  (to which the middle class mestizo adhered). An  anticolonial and indianist revolt and a siege to  colonial power upsurged that covers this period  up to the fall of one of the most bloody neolibe - ral governments of the last decades. In this way  a new period, characterized by the concealment  of a president with aymara origins and a syndi - calist and socialist political standpoint (2005).  Although other leftwing political sectors have  contributed extensively to the Plurinacional state  construction process, the Indianist and Katarist  contribution is undeniable. In this article we  enphasize likewise in the “decolonization pro - cess” and the construction of a true Plurinacional and Communitarian state.
Keywords: Indigenous movement; Indianist and Katarist political parties; Ethnic nationalism; Anticolonial revolt; Internal colonialism; Indigenous self-determination